All‐Solution‐Processed, All‐Organic Flexible Transistor and Circuit Based on Dry‐Transfer Polymer Films - Shanlei Guo; Jing Sun; Xue Wang; Yanhong Tong; Qingxin Tang; Yichun Liu (Advanced Electronic Materials)
Abstract Organic thin‐film transistors (OTFTs), the key component of the future wearable electronics, have the outstanding advantages including cost‐effective, low‐temperature, and large‐area production. However, all‐organic TFTs with an all‐solution process and high‐precision electrode pattern remain an enormous challenge due to dissolution and incompatible fabricated processes between functional layers. Here, a universal, solution‐free transfer and lamination strategy is proposed, which is totally compatible with various commercial materials and fabricated technique in transistors. Excellent mechanical stability, good operation, high‐precision electrode patterns, and outstanding conformability are observed in the all‐organic TFTs. Moreover, as a proof‐of‐utility for the strategy, the all‐organic complementary inverters are fabricated based on all dry‐transfer processes with gain value of 11.2 and stable properties in 30 days in the air. This work provides a universal, solution‐free transfer and lamination strategy to fabricate high‐precision, all‐solution‐processed, all‐organic devices fully maximizing the great advantages of organic materials for the future multilayered functional, commercialized, and industrialized flexible electronics.